Historical and philosophical basis of culture of health - Крошка, С. А. (Slobozhanskyi Herald of Science and Sport, 2011)
In the article, the sources of ideas are described about a health from ancient times to contemporaneity. Historical and philosophical basis of culture of health is exposed. Interest is certain in the problem of forming of culture of health in connection with general progress of modern culture trends, by сущностными descriptions of culture of health in becoming physically, mentally and morally to healthy personality.